Sosialisasi Penggunaan Website Dan Aplikasi SIKAPAL Bagi Panglima Laot Dalam Meningkatkan Keefektifan Pelaporan Illegal Fishing - Fadli Afriandi; Resti Auliya; Akhramil Hakimi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Illegal fishing in Aceh Singkil, including destructive fishing practices by fishermen, threatens maritime security, reduces local fishermen's catches, diminishes the welfare of coastal communities, and damages the marine environment. So far, case reporting has been done manually, which is ineffective and slow. To address this issue, the community service team introduced digital technology for reporting illegal fishing. Considering that the Aceh Singkil community is transitioning from traditional to modern practices, socialization of technology usage is crucial. This socialization was conducted through lectures and discussions. As a result, participants, including Panglima Laot and fishermen, understood the importance of technology in their tasks. Evaluations showed an increase in understanding, collective awareness of sustainable marine resource management, and strengthened Panglima Laot's position as a government partner. With this technology, reporting is expected to be faster, more accurate, and more effective in protecting marine ecosystems and improving the welfare of coastal communities. Furthermore, the implementation of digital technology is expected to enhance transparency and accountability in addressing illegal fishing cases. With the web-based reporting system and the SIKAPAL application, each report can be well-documented, facilitating relevant authorities in responding to reports more efficiently and accurately.